Physiological quality and dormancy overcoming in Sclerocarya birrea seeds stored for different periods - , João Rafael Prudêncio dos Santos (2023)
Marula (Sclerocarya birrea) is a species of the family Anacardiaceae, native to the savanna biome in South and East Africa. It is among the most valued native trees of southern Africa due to its medicinal and nutritional properties; however, the dormancy of its seeds makes the production of marula difficult. Thus, the objective of this work was to evaluate the effect of storage times on dormancy breaking and physiological quality of marula seeds. A completely randomized experimental design was used, with four 100-seed replications for evaluating seed biometry. Physiological quality and dormancy breaking were evaluated through treatments consisted of five storage periods: 10 (control), 184, 244, 306, 367, and 428 days after harvest, with four 25-seed replications per treatment. Storing marula seeds under room conditions for 367 days after harvest is recommended for a better physiological quality of the seeds.